Comportamento, dieta e uso do espaço em um grupo de guigó-de-coimbra (Callicebus coimbrai Kobayashi & Langguth 1999) no RVS Mata do Junco Capela-SE - Santana, Marina Marques de (2012)
Callicebus coimbrai is a recently-discovered primate species endangered with extinction due to the ongoing degradation of its natural habitat. Despite recent advances in research, the ecology of this species is still poorly-known. The present study aimed to further our knowledge of the ecology of the species, with the principal objective of guaranteeing its long-term conservation. A group of titis was monitored in the Mata do Junco Wildlife Refige in the municipality of Capela. The study group was initially composed of a breeding pair, an adult, two subadults, and a juvenile, and was monitored between August and December, 2011. Quantitative behavioural data were collected using continuous scan-sampling, with one-minute samples being collected at five-minute intervals. In November, the non-breeding adult disappeared and a pair of twins was born. The animals spent 34.6% of their time at rest, 26.9% feeding, 22.4% moving, 6.9% in social behaviour, 4.7% vocalising, and 2.0% foraging (2.5% miscellaneous). The diet was composed of fruit (62.9%), leaves (28.4%), seeds (5.0%), and flowers (3.6%), with a total of 21 species being exploited. The most frequently-used species were of the families Melastomataceae, Apocynaceae, and Dilleniaceae. Fruit was consumed significantly more frequently during the rainy season, whereas consumption of leaves and flowers increased during the dry season. This variation was accompanied by a shift in the activity pattern, with feeding and moving being significantly more frequent during the rainy season, and rest increasing in the dry. The home range recorded during the study was of 8.7 ha, but was probably underestimated due to the short duration of the study. Overall, the behaviour of the study group was typical of the genus Callicebus, although some differences were observed in comparison with previous studies of C. coimbrai, such as relatively frequent interactions with Callithrix jacchus. The results re-emphasised the tolerance of these animals towards habitat fragmentation, based on the behavioural flexibility and capacity to exploit alternative resources. The study contributed to the consolidation of a database on the ecology of C. coimbrai, which should guarantee the conservation of the species and the ecosystems it inhabits over the long term.